Perovskite thin film and preparation method and application thereof

By adding 5-bromoacetyl-2-hydroxybenzeneamide to the precursor solution of the perovskite film to adjust its crystallization kinetics process, the problem of weakening light absorption capacity and increasing defects when the thickness is reduced is solved, and a translucent solar cell with high efficiency and high transparency is achieved.

CN119654044AActive Publication Date: 2025-03-18HUNAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411847942.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

When existing translucent perovskite solar cells reduce the film thickness to achieve translucent characteristics, they will weaken the light absorption capacity and reduce the photoelectric conversion efficiency of the battery. In addition, low-thickness films are prone to form physical defects such as holes, affecting their performance.

Method used

By adding 5-bromoacetyl-2-hydroxybenzeneamide to the precursor solution of the perovskite film, its crystallization kinetics process is adjusted, and the nucleation speed is promoted and the crystal growth rate is slow, thereby obtaining a perovskite film with high crystallinity, low defect density and no holes.

Benefits of technology

The high-quality preparation of perovskite films is achieved, which improves its grain size and crystallinity, reduces defect density and eliminates hole defects, thereby improving the energy conversion efficiency of translucent solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654044A_ABST
    Figure CN119654044A_ABST
Patent Text Reader

Abstract

The invention provides a semitransparent perovskite thin film, the chemical formula of a perovskite material is FA < 0.8 > MA < 0.15 > Cs0 < 0.05 > Pb < (I < 0.76 > Br < 0.24 >) < 3 >, FA is formamidine, MA is methylamine, Pb is N, N is N, N is N, N is N, N is N, N is N, N is N, N is N, N is N The perovskite material is doped with 5-bromoacetyl-2-hydroxybenzamide, and the perovskite material is doped with the 5-bromoacetyl-2-hydroxybenzamide. According to the perovskite material provided by the invention, an amide group in the 5-bromoacetyl-2-hydroxybenzamide respectively forms a hydrogen bond and a coordinate bond with halogen and uncoordinated Pb < 2 + > ions for interaction, and a hydroxyl group and an acetyl group in the 5-bromoacetyl-2-hydroxybenzamide also can form interaction with perovskite; the crystallization kinetic process of perovskite is regulated and controlled, more uniform nucleation sites are provided, the nucleation speed is high, the crystal growth speed is low, and the perovskite crystal film which is high in crystallinity, large in grain size and free of holes is obtained. The invention also provides a preparation method and application of the semitransparent perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cells, and in particular relates to a method for preparing a perovskite film. Background Art

[0002] Semi-transparent solar cells have become a promising new type of photovoltaic technology, with great application potential in the fields of power generation windows, building-integrated photovoltaics and tandem solar cells. Semi-transparent solar cells are a new type of solar cell technology developed on the basis of traditional solar cells. They can not only collect sunlight to generate electricity to the maximum extent, but also allow unabsorbed light to pass through the solar cell to achieve the effect of light transmission, or further use this part of light to generate electricity for the bottom cell; semi-transparent solar cells are mainly composed of rigid or flexible transparent conductive substrates, hole transport layers, photoactive layers, electron transport layers and transparent back electrodes; among them, the photoactive layer mainly includes organic semiconductors, organic dyes and halide perovskite materials.

[0003] In recent years, halide perovskite has the advantages of adjustable band gap, high absorption coefficient, and low manufacturing cost. It is a photoactive material with excellent performance and is widely used to build semi-transparent solar cells. In practical applications, semi-transparent perovskite solar cells (ST-PSCs) need to have both high efficiency and high transparency. Among them, the semi-transparent characteristics of the device can be achieved by reducing the thickness of the perovskite film. However, as the film thickness decreases, the light absorption capacity of the perovskite active layer will be weakened, reducing the current of the solar cell ( J SC ), which in turn causes the photovoltaic conversion efficiency (PCE) of the battery to drop sharply (Adv. Mater.2023, 35, 2206574). Therefore, there is a trade-off between the efficiency and transmittance of perovskite films. In addition, low-thickness perovskite films (less than 200 nm) with semi-transparent properties and thicker (400-600 nm) perovskite films have different crystallization kinetics. Specifically, the research paper (Adv. Funct. Mater. 2023,230741, https: / / doi.org / 10.1002 / adfm.202307471)It is proposed that the nucleation rate and crystal growth rate of low-thickness perovskite films with a thickness of less than 200nm are relatively fast during the crystallization process, which will lead to low crystallinity of the perovskite film, while the grain size becomes smaller, the grain boundaries increase, and the defects also increase. In addition, the research paper (ACS Energy Lett.2024, 9, 6, 2936) points out that since the perovskite film grows from bottom to top on the substrate, the low-thickness film is more likely to form physical defects (such as holes) during the crystallization process than the thicker perovskite film. Therefore, how to prepare high-quality semi-transparent perovskite films is a key factor in realizing high-performance semi-transparent solar cells. It can be seen that the development of a method for preparing a semi-transparent perovskite film with low defect density, high crystallinity and no holes has become an urgent problem to be solved. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a thin perovskite film with low thickness (<200 nm), no holes, low defect density and high crystallinity.

[0005] The second object of the present invention is to provide a perovskite film prepared by the method for preparing the perovskite film.

[0006] The third object of the present invention is to provide a solar cell comprising the perovskite thin film.

[0007] The fourth object of the present invention is to provide an application of the perovskite thin film solar cell.

[0008] The present invention is achieved through the following technical solutions: A perovskite film comprising Perovskite material, whose chemical formula is FA 0.8 MA 0.15 Cs 0.05 Pb(I 0.76 Br 0.24 )3, wherein FA is CH(NH2)2, MA is CH3NH2; and 5-bromoacetyl-2-hydroxybenzamide, as a regulator, is used to regulate the crystallization kinetics of the perovskite material; In the solution of the raw material for preparing the perovskite material, the concentration of 5-bromoacetyl-2-hydroxybenzamide is 2.5-3.5 mg / mL, the concentration of CsI is 5.0 mg / mL, the concentration of bromomethylamine is 6.5 mg / mL, the concentration of iodoformamidine is 53.0 mg / mL, the concentration of lead bromide is 42.5 mg / mL, and the concentration of lead iodide is 134.0 mg / mL; The thickness of the perovskite film is less than 200 nm.

[0009] The method for preparing the perovskite film comprises the following steps: Cesium iodide (CsI), methylamine bromide, iodoformamidine, lead bromide and lead iodide are dissolved in an organic solvent, and then 5-bromoacetyl-2-hydroxybenzamide is added to obtain a precursor solution; The precursor solution is dropped on the surface of the substrate and spin-coated. 10 seconds before the end of spin-coating, the anti-solvent is dropped on the surface of the substrate spin-coated with the precursor solution. Finally, heating and annealing are performed for 30-60 minutes to obtain a perovskite film.

[0010] The organic solvent includes dimethylformamide and / or dimethyl sulfoxide; The volume ratio of dimethylformamide to dimethyl sulfoxide is 4:1; The substrate comprises indium tin oxide glass; The heating temperature is 60°C; The annealing time is 30-60 min.

[0011] The spin coating includes a first spin coating and a second spin coating; The first spin coating is performed at a speed of 1000 r / m and a time of 40 s; The second spin coating speed is 3000r / m and the time is 20s; A perovskite solar cell comprising the perovskite film.

[0012] The perovskite solar cell of the perovskite film comprises, from bottom to top, a transparent conductive glass substrate, a hole transport layer, the perovskite film, an electron transport layer, a hole blocking layer and a back electrode.

[0013] The transparent conductive glass substrate comprises ITO glass; The hole transport layer includes PTAA; The electron transport layer includes C60; The hole blocking layer includes BCP; The back electrode includes Au.

[0014] The method for preparing the perovskite solar cell comprises the following steps: After PTAA is dissolved in a solvent to obtain a PTAA solution, the PTAA solution is dropped onto a transparent conductive glass substrate, the rotation speed is set at 3000 r / m and the coating is performed for 30 seconds, and then the substrate is heated to 120°C and annealed for 20 minutes; The method as claimed in claim 2 is used to load a perovskite film on the surface of a substrate loaded with PTAA; The electron transport layer, the hole blocking layer and the back electrode are sequentially deposited on the surface of the substrate carrying the perovskite film by a vacuum evaporation method.

[0015] The ratio of PTAA to solvent is 2 mg: 1 mL The solvent includes chlorobenzene.

[0016] The perovskite solar cell is used for power generation.

[0017] Compared with the prior art, the present invention brings the following technical effects: The present invention provides a low-thickness hybrid perovskite active film material, which regulates the crystallization kinetics of the precursor solution by adjusting 5-bromoacetyl-2-hydroxybenzamide (BASA), making the nucleation fast and the growth slow, thereby increasing the grain size and crystallinity of the perovskite, reducing the defect state density and eliminating the hole defects in the film. The perovskite film is applied to a semi-transparent solar cell, and the prepared PIN-type solar cell has a higher energy conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The SEM image of the surface of the low-thickness perovskite film prepared in Example 1 is shown Figure 2 The surface SEM image of the low-thickness perovskite film prepared in Comparative Example 1 is shown. Figure 3 The cross-sectional SEM image of the low-thickness perovskite film prepared in Example 1 is shown; Figure 4 The XRD patterns of the perovskite films prepared in Example 1 and Comparative Example 1 with and without the addition of 5-bromoacetyl-2-hydroxybenzamide are shown; Figure 5 The ultraviolet visible light (UV-vis) spectra of the perovskite films prepared in Example 1 and Comparative Example 1 with and without the addition of 5-bromoacetyl-2-hydroxybenzamide are shown; it can be seen from the figure that the film with the addition of 5-bromoacetyl-2-hydroxybenzamide has a higher absorbance and a stronger ability to absorb light, which means that the film is denser and has no holes; Figure 6 The photoluminescence (PL) spectra of the perovskite films prepared in Example 1 and Comparative Example 1 with and without the addition of 5-bromoacetyl-2-hydroxybenzamide are shown; it can be seen from the figure that the film with the addition of 5-bromoacetyl-2-hydroxybenzamide has a higher emission spectrum intensity, indicating that the film is denser, has no holes, and has a low defect density; Figure 7 The schematic diagram of the semi-transparent perovskite solar cell structure is shown; the semi-transparent cell structure from bottom to top is as follows: 1- Transparent conductive glass: Indium Tin Oxide (ITO) glass; 2-Hole transport layer: poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA); 3-Perovskite layer: FA 0.8 MA 0.15 Cs 0.05 Pb(I 0.76 Br 0.24 )3, where FA is CH(NH2)2 and MA is CH3NH2 4-Electron transport layer: Fullerene C60; 5-Hole blocking layer: 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP); 6-Metal back electrode: gold (Au); Figure 8 The current-voltage curve of the semi-transparent perovskite solar cell prepared in Example 4 is shown. DETAILED DESCRIPTION

[0019] The present invention provides a perovskite film with a thickness of less than 200 nanometers, which is composed of a perovskite material and 5-bromoacetyl-2-hydroxybenzamide. The chemical formula of the perovskite material is FA 0.8 MA 0.15 Cs 0.05 Pb(I 0.76 Br 0.24 )3, where FA is CH(NH2)2 and MA is CH3NH2. The amino group (-NH2) in the amide group of 5-bromoacetyl-2-hydroxybenzamide (BASA, chemical formula C9H8BrNO3) forms a weak interaction with halogens (e.g., I, Br, etc.) in the form of hydrogen bonds (NH…I), and the C=O bond in the amide group interacts with the uncoordinated Pb in the perovskite. 2+ ions form coordination bonds (C=O-Pb); in addition, hydroxyl groups form hydrogen bonds with halogens (e.g., I, Br, etc.), and the C=O bond in the acetyl group also forms hydrogen bonds with Pb 2+The ions form coordination bonds to produce strong interactions. The presence of these hydrogen bonds makes the crystal structure of the perovskite film stable, with larger grain size and higher crystallinity, which enables it to maintain a long-term stability of the crystal structure under long-term sunlight exposure. Moreover, 5-bromoacetyl-2-hydroxybenzamide can also passivate lead defects (divalent lead and zero-valent metallic lead) in the perovskite film, so it will show high energy conversion efficiency. The addition amount of 5-bromoacetyl-2-hydroxybenzamide is: 2.5-3.5 mg / mL, and the optimal concentration is 3.0 mg / mL; when the addition amount is less than 2.5 mg / mL, the molar amount of the group forming a bond with the perovskite in 5-bromoacetyl-2-hydroxybenzamide is insufficient, which will lead to the existence of halogen vacancy defects and uncoordinated divalent lead ion defects; when the addition amount is greater than 3.5 mg / mL, the molar number of the group forming a bond with the perovskite in 5-bromoacetyl-2-hydroxybenzamide is sufficient, and at the same time, the boiling point of 5-bromoacetyl-2-hydroxybenzamide is 420.2°C, and it will remain in the film after the low-temperature annealing is completed, forming point defects, resulting in phase impurity of the film crystal.

[0020] Specifically, the method for preparing the perovskite film comprises the following steps: Cesium iodide (CsI), methylamine bromide, iodoformamidine, lead bromide and lead iodide are dissolved in an organic solvent, and then 5-bromoacetyl-2-hydroxybenzamide is added to obtain a precursor solution.

[0021] The precursor solution is dropped on the surface of the substrate and spin-coated. 10 seconds before the end of spin-coating, the anti-solvent is dropped on the surface of the substrate spin-coated with the precursor solution; finally, heating and annealing are performed for 30-60 minutes to obtain a perovskite film.

[0022] In the process of preparing perovskite films, 5-bromoacetyl-2-hydroxybenzamide also plays a very important role. In the precursor solution, 5-bromoacetyl-2-hydroxybenzamide can form hydrogen bonds with the groups in the raw materials. Therefore, 5-bromoacetyl-2-hydroxybenzamide can regulate the crystallization kinetics of the perovskite precursor solution, provide more uniform nucleation sites during the crystallization process, accelerate the nucleation rate, and slow down the crystal growth rate, thereby obtaining a semi-transparent perovskite film with large grain size, low defect density, and no holes. In particular, when the thickness of the film is less than 200 nanometers, if 5-bromoacetyl-2-hydroxybenzamide is not added, there will be a lot of holes and gaps in the film obtained after annealing. After adding 5-bromoacetyl-2-hydroxybenzamide, the quality of the film is significantly improved.

[0023]

[0024] The organic solvent includes dimethylformamide or dimethylformamide and dimethyl sulfoxide. The effect of the mixed solvent is better than that of a single solvent. This is because dimethyl sulfoxide (DMSO) plays a solubilizing role, making the precursor solution more stable. At the same time, DMSO will chelate with Pb to form an intermediate phase during the perovskite crystallization process, which helps to obtain a crystalline film with higher crystallinity.

[0025] The volume ratio of dimethylformamide to dimethyl sulfoxide is 4:1; the amount of DMSO should be in a relatively appropriate ratio. Too little DMSO will not play a role in solubilization and crystallization regulation, and too much DMSO is not conducive to film formation (because DMSO is more hydrophobic than dimethylformamide DMF, it is more difficult to spread the solution on the substrate during spin coating, resulting in a lower film coverage). The substrate comprises indium tin oxide glass; The heating temperature is 60° C.; too high a temperature will cause the organic components (FA: CH(NH2)2, MA: CH3NH2) in the perovskite to volatilize.

[0026] The annealing time is 30-60 min.

[0027] The spin coating includes a first spin coating and a second spin coating; the first spin coating is at a low speed of 1000 r / m, which mainly plays the role of spreading the solution, and the solvent will not evaporate quickly. The second spin coating is at a higher speed of 3000 r / m, and anti-solvent chlorobenzene is added dropwise at the same time, which can quickly replace DMF and DMSO in the perovskite precursor and quickly crystallize.

[0028] The first spin coating is performed at a speed of 1000 r / m and a time of 40 s; The second spin coating speed is 3000r / m and the time is 20s; A perovskite solar cell comprising the perovskite film.

[0029] The perovskite solar cell of the perovskite film comprises, from bottom to top, a transparent conductive glass substrate, a hole transport layer, the perovskite film, an electron transport layer, a hole blocking layer and a back electrode.

[0030] The transparent conductive glass substrate includes ITO glass; those skilled in the art will appreciate that the transparent conductive glass substrate may also be FTO, but semi-transparent solar cells are usually made of ITO. Preferably, the hole transport layer comprises PTAA; those skilled in the art will appreciate that the hole transport layer may also be made of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) or nickel oxide (NiO). The electron transport layer includes C60; those skilled in the art will appreciate that the electron transport layer may also be made of [6,6]-phenyl C61 butyric acid methyl ester (PC61 BM) The hole blocking layer includes BCP; The back electrode includes Au. A person skilled in the art can understand that the back electrode can also be made of Ag (20 nm), Ag (20 nm) / MoO3 (10 nm), Cu (5 nm) / Ag (15 nm), etc.

[0031] By adjusting the preparation parameters, fixing the concentration of the precursor solution and the spin coating process parameters (rotation speed, acceleration and spin coating time), the thickness of the perovskite film can be precisely controlled to be less than 200nm.

[0032] The method for preparing the perovskite solar cell comprises the following steps: After PTAA is dissolved in a solvent to obtain a PTAA solution, the PTAA solution is dropped onto a transparent conductive glass substrate, the rotation speed is set at 3000 r / m and the coating is performed for 30 seconds, and then the substrate is heated to 120°C and annealed for 20 minutes; The method is used to load a perovskite film on the surface of a substrate loaded with PTAA; The electron transport layer, the hole blocking layer and the back electrode are sequentially deposited on the surface of the substrate carrying the perovskite film by a vacuum evaporation method.

[0033] The ratio of PTAA to solvent is 2 mg:1 mL; The solvent includes chlorobenzene. Those skilled in the art will appreciate that any common organic solvent can be used to implement the present invention. Specifically, dichlorobenzene can be selected.

[0034] Since the perovskite solar cell has a high energy conversion efficiency, it can be applied to power generation.

[0035] The present invention is further described below in conjunction with specific embodiments.

[0036] The manufacturer of 5-bromoacetyl-2-hydroxybenzamide used in the present invention is Thermo Scientific, and it was purchased from J&K Technology Co., Ltd.

[0037] Example 1 Dissolve 5.0 mg of cesium iodide (CsI), 6.5 mg of methylamine bromide (CH3NH3Br, MABr), 53.0 mg of iodoformamide (CH(NH2)2I, FAI), 42.5 mg of lead bromide (PbBr2), and 134.0 mg of lead iodide (PbI2) in 1 mL of a mixed solvent of dimethylformamide (C3H7NO, DMF): dimethyl sulfoxide (C2H6OS, DMSO), with a volume ratio of 4:1 between the two solvents, and add 3 mg of 5-bromoacetyl-2-hydroxybenzamide to the solution. Place the solution bottle on a heating plate and stir at 60°C for 4 hours. After complete dissolution, filter the precursor solution using a 0.22 μm polytetrafluoroethylene (PTFE) filter.

[0038] The precursor solution was dropped onto an indium tin oxide (ITO) glass substrate using a pipette, and the spin coater was set to two-step parameters (1,000 rpm 40s, 3,000 rpm 20s). Ether was dropped onto the perovskite film as an antisolvent 10s before the end of the spin coating. Subsequently, the perovskite film was transferred to a heating plate and annealed at 80-110°C for 30-60 min to obtain a perovskite film.

[0039] Example 2 Dissolve 5.0 mg of cesium iodide (CsI), 6.5 mg of methylamine bromide (CH3NH3Br, MABr), 53.0 mg of iodoformamide (CH(NH2)2I, FAI), 42.5 mg of lead bromide (PbBr2), and 134.0 mg of lead iodide (PbI2) in 1 mL of a mixed solvent of dimethylformamide (C3H7NO, DMF): dimethyl sulfoxide (C2H6OS, DMSO) with a volume ratio of 4:1, and add 2.5 mg of 5-bromoacetyl-2-hydroxybenzamide to the solution. Place the solution bottle on a heating plate and stir at 60°C for 4 hours. After complete dissolution, filter the precursor solution using a 0.22 μm polytetrafluoroethylene (PTFE) filter.

[0040] The precursor solution was dropped onto an indium tin oxide (ITO) glass substrate using a pipette, and the spin coater was set to two-step parameters (1,000 rpm 40s, 3,000 rpm 20s). Ether was dropped onto the perovskite film as an antisolvent 10s before the end of the spin coating. Subsequently, the perovskite film was transferred to a heating plate and annealed at 80-110°C for 30-60 min to obtain a perovskite film.

[0041] Example 3 Dissolve 5.0 mg of cesium iodide (CsI), 6.5 mg of methylamine bromide (CH3NH3Br, MABr), 53.0 mg of iodoformamidine (CH(NH2)2I, FAI), 42.5 mg of lead bromide (PbBr2), and 134.0 mg of lead iodide (PbI2) in 1 mL of a mixed solvent of dimethylformamide (C3H7NO, DMF): dimethyl sulfoxide (C2H6OS, DMSO), with a volume ratio of 4:1 between the two solvents, and add 3.5 mg of 5-bromoacetyl-2-hydroxybenzamide to the solution. Place the solution bottle on a heating plate and stir at 60°C for 4 hours. After complete dissolution, filter the precursor solution using a 0.22 μm polytetrafluoroethylene (PTFE) filter.

[0042] The precursor solution was dropped onto an indium tin oxide (ITO) glass substrate using a pipette, and the spin coater was set to two-step parameters (1,000 rpm 40s, 3,000 rpm 20s). Ether was dropped onto the perovskite film as an antisolvent 10s before the end of the spin coating. Subsequently, the perovskite film was transferred to a heating plate and annealed at 80-110°C for 30-60 min to obtain a perovskite film.

[0043] Comparative Example 1 Dissolve 5.0 mg of cesium iodide (CsI), 6.5 mg of methylamine bromide (CH3NH3Br, MABr), 53.0 mg of iodoformamide (CH(NH2)2I, FAI), 42.5 mg of lead bromide (PbBr2), and 134.0 mg of lead iodide (PbI2) in 1 mL of a mixed solvent of dimethylformamide (C3H7NO, DMF): dimethyl sulfoxide (C2H6OS, DMSO), with a volume ratio of 4:1. Place the solution bottle on a heating plate and stir at 60°C for 4 hours. After complete dissolution, filter the precursor solution using a 0.22 μm polytetrafluoroethylene (PTFE) filter.

[0044] The precursor solution was dropped onto an indium tin oxide (ITO) glass substrate using a pipette, and the spin coater was set to two-step parameters (1,000 rpm 40s, 3,000 rpm 20s). Ether was dropped onto the perovskite film as an antisolvent 10s before the end of the spin coating. Subsequently, the perovskite film was transferred to a heating plate and annealed at 80-110°C for 30-60 min to obtain a perovskite film.

[0045] Example 4 This embodiment provides a method for preparing the semi-transparent perovskite solar cell.

[0046] The semi-transparent perovskite solar cell is a pin-type semi-transparent solar cell, and its device structure is ITO / PTAA / perovskite / C60 / BCP / Au (see Figure 4 ), in which indium tin oxide (ITO) is a transparent conductive glass substrate, poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA) is a hole transport layer, perovskite is an active layer, fullerene C60 is an electron transport layer, 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP) is a hole blocking layer, and gold (Au) is a back electrode.

[0047] The preparation process includes the following steps: ITO glass cleaning: Use glass cleaning agent to thoroughly clean the upper and lower surfaces of the substrate, then place the ITO substrate in the cleaning rack, soak it in distilled water, acetone and isopropyl alcohol in turn, put it in an ultrasonic cleaner for 15 minutes each, and then take it out; finally, put the ITO substrate in an electric hot air drying oven to dry. Before assembling the battery, put the ITO glass in a UV-ozone treatment machine for UV-ozone treatment for 15 minutes.

[0048] Preparation of hole transport layer: Weigh 2 mg of PTAA solid powder, dissolve it in 1 mL of chlorobenzene (CB) solvent and stir it at room temperature to obtain a clear PTAA solution. Then, take an appropriate amount of PTAA solution and drop it on the ITO conductive glass substrate. Set the speed to 3000 rpm for spin coating for 30 s, and then anneal it at 120°C on a constant temperature heating plate for 20 min.

[0049] A semi-transparent perovskite film was prepared on PTAA according to the method in Example 1.

[0050] The electron transport layer, hole blocking layer and gold electrode are deposited by vacuum evaporation technology: the vacuum coating machine needs to complete the evaporation film formation including C60, BCP and Au electrode. The appropriate amount of C60 and BCP powders are placed in the beam source furnace 1 and beam source furnace 2 respectively. After closing the cavity of the coating machine, the mechanical pump is used to perform rough pumping to pump the internal pressure of the cavity from atmospheric pressure to below 5Pa. After closing the rough pumping, the fore valve, baffle valve and molecular pump are opened respectively to continue fine pumping. When the cavity pressure reaches 5×10 -4Pa, the beam source furnace 1 and beam source furnace 2 are programmed to meet the sublimation conditions of C60 and BCP under high vacuum. When the temperature of beam source furnace 1 reaches about 520℃, the film thickness meter senses the discharge (0.2 Å / s) through the crystal oscillator probe inside the chamber, opens the mask and starts evaporation. The thickness of the entire film is also tracked by the film thickness meter. When the thickness of C60 reaches 20nm, the mask is closed; the beam source furnace 2 is operated to make the temperature reach about 150℃, and the evaporation of the BCP barrier layer is completed with a thickness of 7nm. The sample is removed by exhaust and transferred to the mask with an electrode pattern for evaporation of the Au electrode. The above rough extraction and fine extraction steps are repeated. When the chamber pressure reaches 5×10 -4 After the thickness of the Au electrode reaches 20 nm, the voltage is reduced to 0 V, the exhaust gas is removed, and the battery assembly is completed.

[0051] Example 5 The difference from Example 4 is that a semi-transparent perovskite film is prepared on PTAA according to the method in Example 2.

[0052] Example 6 The difference from Example 4 is that a semi-transparent perovskite film is prepared on PTAA according to the method in Example 3.

[0053] Comparative Example 2 The difference from Example 4 is that a semi-transparent perovskite film is prepared on PTAA according to the method in Comparative Example 1.

[0054] The various parameters of the solar cells prepared in Examples 4-6 and Comparative Example 2 are shown. Among them, the efficiency conversion formula is as follows: Efficiency (PCE) = short-circuit current (Jsc) × open-circuit voltage (Voc) × quality factor (FF).

[0055] Table 1

[0056] It can be seen from Table 1 that the battery efficiency is significantly improved after adding 5-bromoacetyl-2-hydroxybenzamide.

Claims

1. A perovskite film, characterized in that: include Perovskite material, whose chemical formula is FA 0.8 MA 0.15 Cs 0.05 Pb(I 0.76 Br 0.24 )3, wherein FA is NH2CH=NH, MA is CH3NH2; and 5-bromoacetyl-2-hydroxybenzamide, as a regulator, is used to regulate the crystallization kinetics of the perovskite material; In the solution of the raw material for preparing the perovskite material, the concentration of 5-bromoacetyl-2-hydroxybenzamide is 2.5-3.5 mg / mL, the concentration of CsI is 5.0 mg / mL, the concentration of bromomethylamine is 6.5 mg / mL, the concentration of iodoformamidine is 53.0 mg / mL, the concentration of lead bromide is 42.5 mg / mL, and the concentration of lead iodide is 134.0 mg / mL; The thickness of the perovskite film is less than 200 nm.

2. The method for preparing a perovskite thin film according to claim 1, wherein: The steps include: Dissolving cesium iodide, methylamine bromide, iodoformamidine, lead bromide and lead iodide in an organic solvent, and then adding 5-bromoacetyl-2-hydroxybenzamide to obtain a precursor solution; The precursor solution is dropped on the surface of the substrate and spin-coated. 10 seconds before the end of spin-coating, the anti-solvent is dropped on the surface of the substrate spin-coated with the precursor solution. Finally, heating and annealing are performed for 30-60 minutes to obtain a perovskite film.

3. The method for preparing a perovskite thin film according to claim 1, wherein: The organic solvent comprises dimethylformamide; or The organic solvent includes dimethylformamide and dimethyl sulfoxide; The volume ratio of dimethylformamide to dimethyl sulfoxide is 9:1 or 4:1 or 7:3; The substrate comprises indium tin oxide glass; The heating temperature is 30-80°C; The annealing time is 30-60 min.

4. The method for preparing a perovskite thin film according to claim 1, wherein: The spin coating includes a first spin coating and a second spin coating; The first spin coating has a speed of 500-1500 r / m and a time of 30-50 s; The second spin coating is performed at a speed of 3000-5000 r / m and for a time of 10-30 s.

5. A perovskite solar cell comprising the perovskite thin film according to claim 1.

6. The perovskite solar cell of the perovskite thin film according to claim 5, characterized in that: From bottom to top, it includes a transparent conductive glass substrate, a hole transport layer, the perovskite film, an electron transport layer, a hole blocking layer and a back electrode.

7. The perovskite solar cell of the perovskite thin film according to claim 6, characterized in that: The transparent conductive glass substrate comprises ITO glass; The hole transport layer includes PTAA; The electron transport layer includes C60; The hole blocking layer includes BCP; The back electrode includes Au.

8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The steps include: After dissolving PTAA in a solvent to obtain a PTAA solution, drop the PTAA solution on a transparent conductive glass substrate, set the rotation speed to 2000-3000 r / m and spin-coat for 20-35 seconds, heat to 100-120° C. and anneal for 10-20 minutes; The method as claimed in claim 2 is used to load a perovskite film on the surface of a substrate loaded with PTAA; The electron transport layer, the hole blocking layer and the back electrode are sequentially deposited on the surface of the substrate carrying the perovskite film by a vacuum evaporation method.

9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The ratio of PTAA to solvent is 2 mg:1 mL; The solvent includes chlorobenzene.

10. The use of the perovskite solar cell according to claim 6, characterized in that: Used in power generation.

Citation Information

Patent Citations

  • Application of ring [6] aryl amide, perovskite layer film precursor material and preparation method and application thereof

    CN117337121A

  • Application of additive in perovskite material, perovskite material and preparation method and application of perovskite material

    CN117979798A